Antecedentes matemáticos del pensamiento lógico de C.S Peirce - Castrillo Criado, Pilar (ENDOXA, 2007)
Peirce was very current ¡n many fields of study, due both to his scientifically informed approach and to the fact that he wrote hundreds of book reviews and newspaper reports on mathematical meetings. We examine here how and to what extend his logical thought was influenced by the leading mathematical ideas of his own time.